Perspektif Burnout Pada Manajer Proyek Di Indonesia - Santoso, Prasidananto Nur; Hartono, Budi (Jurnal Teknik Industri, 2018)
Burnout is a psychological syndrome caused by acute stress that characterized by emotional exhaustion and disability to sustain the work productivity. In the project management context, burnout can reduce productivity and increase the idle work. This research aims to examine the concept of burnout in the context of Indonesian project managers. This research was done by the cross-section survey with the questionnaire based on the job demands-resources (JD-R) concept adopted from some earlier research. The response rate of 27.22 percent obtained from 78 project manager in Indonesia with the results indicate that job resources affect job demands, the job demands affect burnout which affects job satisfaction at least.